Evaluation of Proximate, Phytochemical, and Heavy Metal Content in Black Cumin and Fenugreek Cultivated in Gamo Zone, Ethiopia - Alemu Mekonnen Tura; Markos Dele Debisa; Etalema Desta Tulu; Birhanu Zeleke Tilinti (International Journal of Food Science)
Spices have been recognized to have medicinal properties. Among several spices and medicinal plants, black cumin and fenugreek are very common. Geographical, climatic, and cultivating soil type can change the chemical composition of these spices. The objective of this work is to determine proximate, phytochemical, and heavy metal content in black cumin and fenugreek cultivated in the Gamo zone, Ethiopia. The proximate composition (moisture, ash, fiber, fat, protein carbohydrate, and gross energy) was determined; their content (%) in black cumin is 6.98±0.12, 5.02±2.9, 6.90±0.21, 32.1±0.68, 20.9±0.09, 34.1±0.73, and 498±4.4, respectively, and 6.30±0.35, 4.27±0.17, 9.36±0.25, 12.8±0.41, 30.8±0.09, 46.1±0.52, and 422±1.6, respectively, in fenugreek. The total means of phenolic flavonoids and alkaloids in black cumin are 193±5.3 mg GAE/100 g, 87.6±4.3 mg QE/100 g, and 69.4±4.7 mg AE/100 g, respectively, and 382±11 mg GAE/100 g, 123±3.6 mg QE/100 g, and 37.6±2.2 mg AE/100 g, respectively, in fenugreek. In black cumin and fenugreek collected from Kamba, Daramalo, and Dita woredas, nine heavy metals were determined by using FAAS. The total mean concentrations in mg/kg for detected heavy metals (Fe, Zn, Cu, Mn, and Co) in black cumin are 78.5±5.9, 27.3±1.5, 3.06±0.26, 8.47±0.22, and 10.1±0.37, respectively, and Cr, Ni, Pb, and Cd were not detected in black cumin. Similarly, the concentrations of Fe, Zn, Cu, Mn, Co, and Ni in fenugreek are 168±5.2, 14.8±0.20, 4.76±0.1, 13.7±0.40, 3.66±0.21, and 2.12±0.03, respectively, and Cr, Pb, and Cd were not detected in fenugreek. All the results of determined parameters were compared to previous studies, and the values were in agreement with slight variations. Therefore, black cumin and fenugreek cultivated in the Gamo zone were free from heavy metal toxicity.